2019
DOI: 10.3390/cancers11111812
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic Autophagy Effect of miR-212-3p in Zoledronic Acid-Treated In Vitro and Orthotopic In Vivo Models and in Patient-Derived Osteosarcoma Cells

Abstract: Osteosarcoma (OS) originates from osteoid bone tissues and is prone to metastasis, resulting in a high mortality rate. Although several treatments are available for OS, an effective cure does not exist for most patients with advanced OS. Zoledronic acid (ZOL) is a third-generation bisphosphonate that inhibits osteoclast-mediated bone resorption and has shown efficacy in treating bone metastases in patients with various types of solid tumors. Here, we sought to clarify the mechanisms through which ZOL inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Among these predicted miRNAs that potentially pair to circNFIX, miR-212-3p was a strong candidate in the current work owing to its anti-tumor role in a variety of human malignancies, such as ovarian cancer, glioma and osteosarcoma. [30][31][32] Moreover, miR-212-3p restrained the tumorigenesis of gastric cancer and bladder cancer by inhibiting the expression of a target, such as SRY-box transcription factor 6 (Sox6) and nuclear factor IA (NFIA). 33,34 A previous document demonstrated the tumor suppressive impact of miR-212-3p in NSCLC malignant progression.…”
Section: Discussionmentioning
confidence: 99%
“…Among these predicted miRNAs that potentially pair to circNFIX, miR-212-3p was a strong candidate in the current work owing to its anti-tumor role in a variety of human malignancies, such as ovarian cancer, glioma and osteosarcoma. [30][31][32] Moreover, miR-212-3p restrained the tumorigenesis of gastric cancer and bladder cancer by inhibiting the expression of a target, such as SRY-box transcription factor 6 (Sox6) and nuclear factor IA (NFIA). 33,34 A previous document demonstrated the tumor suppressive impact of miR-212-3p in NSCLC malignant progression.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma (OS) is a bone malignancy originating from osteoid bone tissue which has a high mortality rate (1,2). Despite the effectiveness of therapeutic modalities for OS, including surgical resection, neoadjuvant, or adjuvant radiotherapy or chemotherapy, the rates of mortality and metastasis among patients with the disease are still extremely high.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that ZOL enhanced γ-ray radiation-induced DNA damage and suppressed OSA cell migration and invasion [34,35]. Recently, we also found that it significantly induced autophagy via modulation of microRNA (miRNA) expression [36]. In addition, increasing evidence showed that some miRNAs are involved in regulating tumor progression and relapse [37].…”
mentioning
confidence: 99%